2006
DOI: 10.17221/3921-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and meat quality in Brown fattened young bulls: effect of rearing method and slaughter weight

Abstract: Three groups of Brown fattened young bulls were studied, comparing the effects of rearing method (suckled vs. bucket reared) and of slaughter weight (400 vs. 480 kg). Suckled animals had higher fatness scores (2.2 vs. 1.3), more dissectible fat (14.5 vs. 9.1%), and higher intramuscular fat content (7.8 vs. 4.6%DM), accompanied by better scores in sensory tenderness (5.2 vs. 3.8) than did the bucket-reared ones. Animals slaughtered at a heavier weight showed a higher dressing percentage (57.5 vs. 53.8%), confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
2
1
0
Order By: Relevance
“…In the study conducted by Hennessy and Morris [ 48 ], steers and heifers were subjected to the same rearing managements after weaning in contrast to our study. Our results also confirm those of Picard et al [ 65 ] showing that modifications of the rearing managements during the pre-weaning period had no impact on the fiber properties measured at slaughter on 18-month-old bulls However, Cerdeño et al [ 50 ] showed that the rearing management applied during the pre-weaning period can have an impact on the tenderness of the calf meat. Considering the rearing management applied during the heifers’ whole life, it is possible that the effect on the sensory properties of the flank steak could interact with the rearing managements applied after the weaning period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the study conducted by Hennessy and Morris [ 48 ], steers and heifers were subjected to the same rearing managements after weaning in contrast to our study. Our results also confirm those of Picard et al [ 65 ] showing that modifications of the rearing managements during the pre-weaning period had no impact on the fiber properties measured at slaughter on 18-month-old bulls However, Cerdeño et al [ 50 ] showed that the rearing management applied during the pre-weaning period can have an impact on the tenderness of the calf meat. Considering the rearing management applied during the heifers’ whole life, it is possible that the effect on the sensory properties of the flank steak could interact with the rearing managements applied after the weaning period.…”
Section: Discussionsupporting
confidence: 91%
“…The carcass results of this study match those of Hennessy et al and Greenwood et al [ 48 , 49 ] illustrating that animals with faster growth during the pre-weaning period were slaughtered with heavier carcass weights when the growth and fattening managements were similar. For the same slaughter weight, Cerdeño et al [ 50 ] did not show significant differences on the conformation score and dressing% of calves when different rearing managements were applied during the pre-weaning period. However, if the calves were slaughtered higher, the conformation score and the dressing% of their carcass were improved [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only WHC showed improvement during the aging period, especially on the 10 th day, and this was statistically significant (P<0.001). This is validated by earlier studies (7,11,30,40). On the other hand, studies conducted on the effect of lairage time in Kıvırcık lambs revealed significant differences in WHC and CL values (13,28).…”
Section: Discussionsupporting
confidence: 89%